Phage steering in the presence of a competing bacterial pathogen - Sean Czerwinski; James Gurney (Microbiology Spectrum)
ABSTRACT The rise of antibiotic-resistant bacteria has necessitated the development of alternative therapeutic strategies, such as bacteriophage therapy, where viruses infect bacteria, reducing bacterial burden. However, rapid bacterial resistance to phage treatment remains a critical challenge, potentially leading to failure. Phage steering, which leverages the evolutionary dynamics between phage and bacteria, offers a novel solution by driving bacteria to evolve away from virulence factors or resistance mechanisms. In this study, we examined whether phage steering using bacteriophage Luz19 could function in the presence of a competing pathogen, Staphylococcus aureus (SA) (USA300), while targeting Pseudomonas aeruginosa (PAO1). Through in vitro co-evolution experiments with and without the competitor, we observed that Luz19 consistently steered P. aeruginosa away from the Type IV pilus (T4P), a key virulence factor, without interference from SA. Genomic analyses revealed mutations in T4P-associated genes, including pilR and pilZ, which conferred phage resistance. Our findings suggest that phage steering remains effective even in polymicrobial environments, providing a promising avenue for enhancing bacteriophage therapy efficacy in complex infections.IMPORTANCEPhage steering—using phages that bind essential virulence or resistance-associated structures—offers a promising solution by selecting for resistance mutations that attenuate pathogenic traits. However, it remains unclear whether this strategy remains effective in polymicrobial contexts, where interspecies interactions may alter selective pressures. Here, we demonstrate that Pseudomonas aeruginosa evolves phage resistance via loss-of-function mutations in Type IV pilus (T4P) when challenged with the T4P-binding phage Luz19 and that this evolutionary trajectory is preserved even in the presence of a competing pathogen, Staphylococcus aureus. Phage resistance was phenotypically confirmed via twitching motility assays and genotypically via whole-genome sequencing. These findings support the robustness of phage steering under interspecies competition, underscoring its translational potential for managing complex infections—such as those seen in cystic fibrosis—where microbial diversity is the norm.